Priprava in zaščita operativnega polja - Tancar, Majda (Obzornik zdravstvene nege, 1979)
The author presents the possibilities of the intraoperative infection and deals with the aseptic measures which are to be undertaken in the operating theatre and strictly observed by the operating team. Thechniques of cleaning and covering the operation area are presented. Some problems related to the above issue still remain to be solved. There is a need of cooperation between the ecological and microbiological sciences as well as the chemopharmaceutical industry and the medical staff who apply the new achievements to the daily practice.